Horn Fly Haematobia irritans irritans (Linnaeus) (Insecta: Diptera: Muscidae) - Dan Fitzpatrick; Phillip E. Kaufman (EDIS)
The horn fly is one of the most economically important pests of cattle worldwide. Just in the United States, hundreds of millions of dollars in losses are attributed to the horn fly annually, while additional millions are spent annually on insecticides to reduce horn fly numbers. Learn more about this pernicious obligate blood-feeding ectoparasite in this 7-page fact sheet, written by Dan Fitzpatrick and Phillip E. Kaufman, and published by the UF Department of Entomology and Nematology, April 2011.